2014
DOI: 10.1074/jbc.m114.564567
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Induces Cell Death in Human Cancer Cells via Enhancing Lysosomal Function and Lysosomal Degradation of Ferritin

Abstract: Background: Artesunate is capable of inducing cell death in cancer cells. Results: Artesunate accumulates in lysosomes and promotes lysosomal function and ferritin degradation, leading to mitochondrial reactive oxygen species production and eventually cell death. Conclusion: Intracellular iron and ferritin degradation is essential for artesunate-induced lysosomal activation and cell death. Significance: This work reveals a novel mechanism underlying artesunate-induced cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 68 publications
5
115
0
Order By: Relevance
“…3I), indicating the important role of iron. In contrast, pretreatment with 50 μM DFO, a specific iron chelator [9,17], significantly prevented ARS-induced cell death (Fig. 3I), demonstrating that ARS induced iron-dependent apoptosis in HepG2 cells.…”
Section: Ars Induces Ros-independent Intrinsic Apoptosismentioning
confidence: 66%
See 2 more Smart Citations
“…3I), indicating the important role of iron. In contrast, pretreatment with 50 μM DFO, a specific iron chelator [9,17], significantly prevented ARS-induced cell death (Fig. 3I), demonstrating that ARS induced iron-dependent apoptosis in HepG2 cells.…”
Section: Ars Induces Ros-independent Intrinsic Apoptosismentioning
confidence: 66%
“…A general consensus for the selective cytotoxicity of ARTs towards tumor cells is that higher concentration of intracellular iron of tumor cells makes ARTs release excess ROS to trigger proapoptotic signal pathways [4,8,14]. This hypothesis has been proved by the evidences that decreasing cellular iron by either blocking the transferrin receptors or pretreatment with DFO can markedly abrogate ARTs activity, and that preloading cancer cells with iron or iron-saturated transferrin can remarkably increase the cytotoxicity of ARTs in different cancer cell lines [17,[43][44][45][46]. However, our data that although ARS induced cellular ROS generation (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…But under specific circumstances ferritin can behave as a pro-oxidant molecule. For example, artesunate, the anti-malarial drug with anti-tumor activity, was shown to induce cell death via enhancing lysosomal degradation of ferritin [50]. It is becoming accepted that ferritin can behave a pro-oxidant manner when certain trigger molecules can liberate the sequestered iron, or open the gated pores of ferritin [51].…”
Section: Discussionmentioning
confidence: 99%
“…A study also identified that propranolol decreases HIF-1α, reduces downstream VEGF, VEGFR-1 and VEGFR-2 and the expression of monocyte chemoattractant protein-1, thus inhibiting angiomatous proliferation; however, there were no significant differences in the expression of matrix metalloproteinases (44). Artesunate, a compound isolated from a traditional Chinese medicine plant, is currently being evaluated for anti-tumor activity (45,46). Chinese medicine workers first identified artemisinin in the early 1970s as an effective antimalarial ingredient, extracted from sweet wormwood (Artemisia annua) (47).…”
Section: Discussionmentioning
confidence: 99%